Differences in experiences of care between patients diagnosed with metastatic cancer of known and unknown primaries: mixed-method findings from the 2013 cancer patient experience survey in England. Issue 9 (27th September 2017) - Wagland, Richard; Bracher, Mike; Drosdowsky, Allison; Richardson, Alison; Symons, John; Mileshkin, Linda; Schofield, Penny
Abstract : Objectives: To explore differences in experiences of care reported in the Cancer Patient Experience Survey (CPES) between patients with cancer of unknown primary (CUP) and those with metastatic disease of known primary (non-CUP); to determine insights pertaining to the experiences of care for CUP respondents from free-text comments. Design: Two separate, but related, studies, involving secondary analysis of existing data. Using frequency matching of CUP and non-CUP patients, statistical comparisons of responses to CPES questions were conducted. Free-text comments from CUP respondents were analysed thematically. Setting and participants: The CPES questionnaire comprises 63 closed questions measuring 8 areas that relate to experience of care and 3 free-text questions. Questionnaires were mailed to all adult patients (aged ≥16 years) in England with cancer admitted to hospital between 1 September 2013 and 30 November 2013. Results: Matched analysis of closed response items from 2992 patients found significant differences between CUP (n=1496) and non-CUP patients (n=1496): CUP patients were more likely to want more written information about their type of cancer and tests received, to receive their diagnosis from a general practitioner (GP) and have seen allied health professionals, but less likely to have understood explanations of their condition or had surgery. Freetext responses (n=3055) were coded into 17 categories and provided deeper insight regarding patient information and interactions with GPs. CPES data may include a preponderance of patients with favourable CUP subtypes and patients initially identified as CUP but whose primary was subsequently identified. Conclusions: These are the first large-scale studies to explore the experiences of care of CUP patients. The significant differences identified between the experiences of CUP and non-CUP patients suggest CUP patients require more psychosocial support and specific interventions to manage diagnostic uncertainty and the multiple investigations many CUP patients face. Substantial limitations were identified with the CPES data, emphasising the need for prospective studies.